How do adolescents with cerebral palsy participate? Learning from their personal experiences. (1st June 2018) - Wintels, Sophie Catharina; Smits, Dirk‐Wouter; van Wesel, Floryt; Verheijden, Johannes; Ketelaar, Marjolijn; ,
Abstract: Background: Participation in society can be difficult for adolescents with cerebral palsy (CP). Information is often based on quantitative studies, and little is known about their personal participation experiences. Objective: The aim of this study was to examine the participation experiences of adolescents (aged 12‐17 years) with CP. Methods: A qualitative participatory research method was used. Twenty‐three semi‐structured open interviews were conducted with 13 male and 10 female adolescents (mean age 15 years) with CP. An interview checklist was developed jointly with adolescents with CP. This checklist ensured that the adolescents reflected on various participation areas, that is school, sports, health care and work. The analysis was based on principles of grounded theory. Findings: From the adolescents' experiences, 4 key categories were identified. One concerned participation, as such, expressed as "My participation experiences, " including experiences, thoughts and feelings while participating in daily life. Three other categories concerned factors that influence participation experiences, expressed as "My disability, " "Me as a person" and "My environment." These 4 categories together formed a model showing the interactions and dynamics of participation according to adolescents with CP. Conclusion: Adolescents with CP expressed their participation experiences, including various important influencing factors. This study conceptualized these experiences into a dynamic model. This experience‐based participation model may provide new, personalized perspectives for practice, for instance in rehabilitation, but also for schools and sports (or sports clubs) attended by adolescents. Focusing on personal and environmental factors might be the key to successful participation.